Challenges faced in the conversion of a tertiary healthcare centre into a COVID-19 hospital and developing a free-standing isolation centre in India - Ratre, Brajesh Kumar; Kumar, Balbir; Garg, Rakesg; Vig, Saurabh; Pandit, Anuja; Bhopale, Shweta Arun; Bhatnagar, Sushma (International Journal of Infection Control, 2022)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) causes coronavirus disease 2019 (COVID-19), which is a highly virulent disease associated with high mortality. Its outbreak into a pandemic has challenged the healthcare system of most countries around the world. A large number of infectious diseases hospitals are the need of hour to counteract this worrying infection. However, it is not possible to build such hospitals on a large scale within a short period of time; the only possibility is to convert existing healthcare facilities into COVID-19 facilities. The Centers for Disease Prevention and Control (CDC) has released guidelines for the preparation of COVID-19 hospitals, but execution at the ground level comes with many challenges. Here, we share our experience and the challenges we faced during the preparation of a tertiary healthcare centre into a COVID-19 centre, with the hope that it will help other institutions to prepare.